Polygamy as a Conditional Legal Concession (Rukhsah): A Maqasid al-Shariah Evaluation of Islamic Family Law in Indonesia - Novia Sri Rahayu; Adjie Tara Saputra; Siti Zubaidah (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
Polygamy remains one of the most debated issues in Islamic law, particularly amid growing demands for gender justice and the transformation of modern family structures. Although studies on polygamy from the perspective of maqasid al-shariah have expanded considerably, most prior research treats the concepts of rukhsah and maslahah in isolation, leaving a gap in integrated evaluative frameworks for assessing the substantive validity of polygamy on a case-by-case basis. This article aims to address that gap by analyzing polygamy through the conceptual relationship between rukhsah (legal dispensation) and maslahah (hierarchical public interest), and evaluating it against the five objectives of maqasid al-shariah, with specific reference to Islamic family law regulation in Indonesia. The study employs a qualitative-normative approach through library research, utilizing comparative analysis (muqaranah) of classical and contemporary usul al-fiqh sources alongside recent socio-legal studies. Three principal findings emerge: first, polygamy holds the status of a conditional rukhsah ibahah - a cause-bound legal dispensation, not a self-standing textual permission; second, the maslahah arguments advanced in support of polygamy operate only at the hajiyyah (secondary) level, while the potential mafsadah it produces - psychological neglect, economic instability, and domestic conflict - threatens interests at the daruriyyah (primary) level, rendering generalized justifications hierarchically untenable; third, Indonesia's regulatory framework is structurally consistent with the maslahah hierarchy, yet persistent implementation gaps - most notably the prevalence of unlicensed polygamy - critically undermine the realization of substantive maslahah. The principal contribution of this article lies in unifying the rukhsah-maslahah framework as a single evaluative lens, shifting the central question from